Preliminary study on the milk producing ability of Ciuta sheep - Greco, Margherita; Lopez, Annalaura; Moretti, Vittorio Maria; Mattiello, Silvana; Marcolli, Beatrice; Celozzi, Stefania; Bellagamba, Federica (Frontiers in Animal Science, 2025)
This study evaluated milking performance and compositional characteristics of milk from ten Ciuta ewes maintaining concurrent lamb suckling throughout an 11-week experimental period. Daily milk yield averaged 345 ± 115g per animal during single milking sessions, with peak individual performances reaching 698g, while lambs continued partial milk consumption. Compositional analysis revealed lactose concentrations of 4.8 ± 0.2%, protein levels of 5.8 ± 0.5%, and fat content of 4.6 ± 1.2%. Somatic cell count remained consistently below 250,000 cells/mL, indicating a good mammary health status. (mean 100 ± 103 cells/mL) The fatty acid profile demonstrated nutritionally favourable characteristics, including an optimal n-6/n-3 ratio of 1.43, alongside significant proportions of branched-chain fatty acids (2.94 ± 0.4%) and conjugated linoleic acid (1.24 ± 0.3%). Observations on udder morphology indicate the potential for favourable udder traits that require further investigation. Behavioural assessment during milking procedures showed progressive adaptation of Ciuta ewes, with discomfort signs declining across the trial duration. Individual variation in milking temperament suggested potential for selection and improvement for adaptation to the milking routine. The outcomes from this study provided original knowledge, suggesting a promising integration of Ciuta sheep into milking while maintaining their traditional rusticity and resilience.